The robustness of the F-test to spatial autocorrelation among regression disturbances - Walter Krämer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
It is shown that the null distribution of the F-test in a linear regression is rather non-robust to spatial autocorrelation among the regression disturbances. In particular, the true size of the test tends to either zero or unity when the spatial autocorrelation coefficient approaches the boundary of the parameter space.
Keywords: 519; F-test; size; spatial autocorrelation